Retrospective and Analytical Study of the Doctrine Related Pharmaceutical Polymorphism and Patents - Madrigal Redondo, German (2015)
Called pharmaceutical polymorphism to change of the crystal structure of a substance when it is in its solid state, this has generated a controversy over whether or not to enjoy protection for patents for invention, and that it could limit or delay the access of generic drugs to health care centers, or services, this study aims to define the main technical characteristics of pharmaceutical polymorphs and determine its patentability under Costa Rican law, such legislation also compared with the doctrine poured into other countries, mainly the United States of America. Methodology: Written information sources and electronic media since 1850 to February 2014 were revised, data were collected and information was placed in an instrument that selects the main themes. Then it was analyzed by triangulation and conclusions were made by technical and legal criteria. Results: Among the main results the eligibility of patentable matter was determined against the non-patentable, the main technical criteria of pharmaceutical polymorphs for a prior art study were established and the differences between the US and Costa Rican law doctrine on the subject of polymorphism and patents was determined.